Desenvolvimento de sensores eletroquímicos utilizando nanomateriais para a determinação de espécies de interesse farmacêutico e ambiental - Figueiredo Filho, Luiz Carlos Soares de (2014)
In this work the development of new sensors using nanomaterials is decribed. Glassy carbon electrode modified with gold nanoparticles and functionalized multi-walled carbon nanotubes within a dihexadecyl phosphate film was fabricated and applied to determine diquat in natural water samples by square wave voltammetry (SWV). The analytical curve was linear in the diquat concentration range from 3.1 × 10−8 to 3.0 × 10−6 mol L−1 with a limit of detection (3 blank/slope of analytical curve) of 1.4 × 10−8 mol L−1. The performance of this electrode was compared with a commercially screen printed electrode from dropsens. The determination of linuron in natural water samples and commercial products was successfully performed using the boron doped diamond with good linear range, repeatability, sensitivity and stability. Moreover, the electrode had the analytical characteristics compared with the same electrode modified with platinum nanoparticles. A glassy carbon electrode with dihexadecyl phosphate film containing platinum nanoparticles was developed to determine linuron and carbendazim in natural waters, orange juice and commercial products by pulse diferential voltammetry (DPV) and square wave voltammetry (SWV) techniques. The detection limits obtained were 6.1 × 10−10 and 1.5 × 10−9 mol L−1 for linuron and carbendazim using SWV, respectively, and the obtained results were in agreement at a 95% confidence level with those results obtained using a high performance liquid chromatography method. Glassy carbon electrode modified with nickel oxide nanoparticles and functionalized multi-walled carbon nanotubes within a dihexadecyl phosphate film was fabricated and applied to the simultaneous determination of dopamine and epinephrine by DPV. The analytical curve obtained shown a linear range from 7.0 × 10−8 to 4.8 × 10−6 and 3.0 × 10−7 to 9.5 × 10−6 mol L−1 for dopamine and epinephrine, respectively. Both analytes were determined in three different synthetic samples of biological fluids (lung fluid, cerebrospinal fluid and human serum) with an acceptable relative standard deviation for the addition and recovery test. Graphene and graphite paste electrodes were also investigated in this thesis. Initially, graphene and graphite were characterized morphologically (RAMAN and XPS), as the obtained pastes. Moreover, the proposed paste electrodes were characterized electrochemically through well-known electrochemical probes as hexacyanoferrate (II) potassium, hexamine ruthenium chloride (III) and hexacloroiridiate (III) sodium. After this study, analytical curves for ascorbic and uric acids were built. It was observed that no significant analytical advantages were obtained when graphite was replaced by graphene in the pastes. The electrochemical of graphene and reticulated vitreous carbon three-dimensional electrodes was first explored in this work. It was observed that due to the hydrophobic nature of the graphene three-dimensional electrode, its application is not favorable in aqueous solutions. Furthermore, this material showed good electrochemical characteristics using ionic liquids as supporting electrolyte, better HET and higher current to electrochemical probes hexacyanoferrate (II) potassium, hexamine ruthenium (III) chloride, ferrocene and N,N,N',N'-tetramethyl-p-phenylenediamine compared with the three-dimensional reticulated vitreous carbon electrode.